DOI: 10.11606/t.88.2006.tde-26072006-135429
|View full text |Cite
|
Sign up to set email alerts
|

"Estudo de concretos de alto desempenho frente à ação de cloretos"

Abstract: Aos meus pais, Vera e Jesus, e aos meus irmãos, Fabiana e Rodrigo. AGRADECIMENTOSPrimeiramente gostaria de agradecer ao meu orientador Jefferson Liborio, pela valiosa oportunidade que me foi concedida no início desta pesquisa, pela dedicação, apoio, incentivo, confiança e, claro, pela amizade estabelecida durante esses anos.Aos professores Ênio Pazini Figueiredo (UFG), Sebastião Elias Kuri (UFSCar) e Silvia Selmo, (EPUSP) pela extrema competência e auxílio na escolha e análise dos métodos experimentais na área… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0
6

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 13 publications
0
6
0
6
Order By: Relevance
“…These results were expected since they were the same concretes that obtained lower capillary absorption index, as discussed previously. Silva (2006) realized the same tests on high performance concretes with 5 and 10% silica fume, and after 16 cycles drying and wetting cycles, obtained a reduction in the depth of penetration of 1.9 mm and 2.7 mm, respectively, compared to the reference concrete, which had a penetration front of 5.7 mm. Regarding the nanosilica addition, although the present work has not obtained satisfactory results, Revista ALCONPAT, 8 (2), 2018: 138 -149 Evaluation of nanosilica effects on concrete submitted to chloride ions attack T. Zanon, R. Schmalz, F. G. S. Ferreira 148 some studies indicate that 3% and 6% colloidal nanosilica addition in mortars could reduce 70% and 77% 28-day chlorides migration, respectively, in comparison to reference mortars (Joshaghani;Moeini, 2017).…”
Section: Chloride Ions Penetrationmentioning
confidence: 79%
See 1 more Smart Citation
“…These results were expected since they were the same concretes that obtained lower capillary absorption index, as discussed previously. Silva (2006) realized the same tests on high performance concretes with 5 and 10% silica fume, and after 16 cycles drying and wetting cycles, obtained a reduction in the depth of penetration of 1.9 mm and 2.7 mm, respectively, compared to the reference concrete, which had a penetration front of 5.7 mm. Regarding the nanosilica addition, although the present work has not obtained satisfactory results, Revista ALCONPAT, 8 (2), 2018: 138 -149 Evaluation of nanosilica effects on concrete submitted to chloride ions attack T. Zanon, R. Schmalz, F. G. S. Ferreira 148 some studies indicate that 3% and 6% colloidal nanosilica addition in mortars could reduce 70% and 77% 28-day chlorides migration, respectively, in comparison to reference mortars (Joshaghani;Moeini, 2017).…”
Section: Chloride Ions Penetrationmentioning
confidence: 79%
“…Among these different aggressive agents present in environment are chloride ions and their ability to initiate reinforcement corrosion, even when the solution contained in concrete pores has high pH. In addition, after their reaction with steel, chloride ions are not fixed and are available to continue the reaction (Silva, 2006). These peculiarities make chloride's attack one of the main mechanisms of concrete structures degradation.…”
Section: Introductionmentioning
confidence: 99%
“…Allied to this fact, the presence of small cracks caused by the drying/wetting cycle and by expansion due to the fact that the onset of the corrosion process caused the concrete resistance to decline again, reaching extremely low values at the end of the test. Silva [21] associated this fact to the samples' higher moisture content. It was found that until this inversion in behavior occurred (in this study, after five months of analysis), the samples with various red mud contents behaved similarly to the reference samples (without red mud), and even better at some points.…”
Section: Electrochemical Impedance Spectroscopy (Eis)mentioning
confidence: 97%
“…According to some studies [14,21], the rebar is in the process of corrosion if the diameter of semicircle formed at low frequencies is decreased, as observed in the Nyquist diagram. Therefore, the lower the R e values, the more advanced the corrosion process.…”
Section: Electrochemical Impedance Spectroscopy (Eis)mentioning
confidence: 99%
“…In order for corrosion of steel reinforcement to occur, it is necessary to have four elements: the conductor, which is the steel bar itself, the electrolyte (water) to conduct the ions, the oxygen that forms the corrosion products and a difference of potential for formation of two distinct areas (the ones of anodic and cathodic nature). This latter factor can be caused by different intensities of concrete densification, differences in aeration, humidity or salt concentrations (Silva, 2006). The frequency of corrosion and the problems associated with it show the need to find solutions that contribute to minimize this deterioration process and its evolution in reinforced concrete structures (Vieira, 2003).…”
Section: Introductionmentioning
confidence: 99%